A Confirmatory Analysis of the Duties of Children and Parents Based on Ephesians 6:1–4 among the Congregation of the Bethel Church of Indonesia Sungai Yordan. - Orta Nia Sinoy; Sri Wahyuni; Fendi (Gereja Alkitab Anugerah Kadoudan, 2025)
Christian families play a vital role in shaping children’s faith, character, and relational life. Ephesians 6:1–4 emphasizes a balanced responsibility between children, who are called to obey and honor their parents, and parents, who are responsible for nurturing their children in love and the instruction of the Lord. However, in congregational practice, these principles are not always consistently understood or applied. This study aims to confirm the level of congregational understanding regarding the duties of children and parents based on Ephesians 6:1–4 and to identify the most dominant dimension influencing this understanding. This research employed a quantitative approach using a survey method involving 25 respondents from the Bethel Church of Indonesia Sungai Yordan, Tanjung Maya, Sanggau, West Kalimantan. Data analysis included validity, reliability, and normality tests, a 5% Confidence Interval, linear regression analysis, and one-way ANOVA using SPSS version 25. The findings indicate that the confirmation of children’s and parents’ duties falls within the moderate category. Furthermore, the dimension of parents’ duties toward children emerged as the most dominant factor, contributing 84.4% to the overall confirmation. These results highlight the central role of parental responsibility in fostering Christian family relationships grounded in biblical principles.